Fryderyk Chopin’s correspondence from the perspective of body studies. The discovery of corporeality - Sosnowska, Danuta (Katedra Muzykologii, Wydawnictwo Naukowe PTPN, Wydawnictwo Naukowe UAM, 2010)
The author analyses Fryderyk Chopin’s correspondence within the context of the new humanities field of body studies. The socio-cultural anthropology of the body has been an object of study since the 1980s. It has enabled the extraction of the picture of a cultural body inscribed in Chopin’s correspondence, and it has also shown how his conception of his own soma and of the bodies of other people diverge from the Romantic convention of writing about corporeality. In the age of romanticism, sickness and physical weakness were glorified like a gift and a badge of spiritual aristocracy. A suffering and frail complexion became a value in the salons – a laissezpasser to the world of artistic sensitivity. Chopin never succumbed to that fashion. His record of his corporeal experience is strikingly un-Romantic, as can be seen, for example, when comparing it with the narration of sickness contained in the correspondence of Zygmunt Krasiński. The corporeal experience displayed by the great musician is striking in its modernity. Chopin rejects the Romantic lyricisation of sickness; his utterances are pithy, dominated by sarcasm and even physiological brutality, and the style of his description of corporeality employs grotesqueness, irony and absurdity. Human subjectivity sensed through the body paints a picture of a fragmentary, disharmonious self; people reveal themselves to the eyes of others not as a whole, but as an abbreviation, a representative detail. Visions of mechanised bodies, whose behaviour and actions are hyperbolised by the musician, bring us – especially during the last years of Chopin’s life – into a world where corporeality is a source of strangeness, and even repugnance. In the conclusion of the article, the author denies that Chopin’s music can be directly translated into a moving picture: she states that neither his illness nor any other experiences of his bodily existence can be treated in an illustrative way that purports to “illuminate” his music directly.
Keywords: Chopin’s correspondence; Somatic studies; Cultural body; sickness; Irony; Grotesque; Fragmentary self; Music and image